Car Cariogenics Pattern Relationships And Habits Of Dental Basing With Teening Of Dental Caries On Children In SDN Kampung Dalem 6 Kediri City - Esmenia Maria Rodrigues Soares; Atik Setiawan; Nuryeny H (Journal of Hospital Management and Services, 2020)
A primary school child is a vulnerable group dental and mouth disease because it still has a habit of lacking self support to dental health , and one of the dental diseases experienced by dental caries. The purpose of research to know dietary relationships and the habit of brushing teeth with the onset of dental caries in children at SDN Kampung Dalem 6 Kediri. Observational research design with cross sectional approach. Population of all children aged 7-8 years in SDN Kampung Dalem 6 Kediri City as many as 60 people, sa mpel as many as 60 respondents. Data collection with questioner and observation for 1 weekthen analyzed by Spearman test. The results showed almost half the respondents has a diet with sufficient category of 28 respondents (46.7%), almost half of respondents has Kabiasaan brushing teeth with enough category that is as much as 27 respondents (45%), half of respondents suffered dental caries type 3 that is enough 27 respondents (45%), and there is a relationship between eating patterns and the habit of brushing teeth with the onset of dental caries in children at SDN Kampung Dalem 6 Kediri (Spearman with p value = 0.00 0 0 <α 0.05). Diet and habits of a good brushing teeth properly will reduce the risk for developing dental caries due for wich good diet and good habits to brush their teeth properly can reduce exposure to the causative agent of dental caries.